Dancing through fire - Lasky, Kathryn (New York : Scholastic, 2005)
A story inspired by Edgar Degas's famous 1878 painting "L'Étoile," or "Dancer on the Stage," in which Sylvie Bertrand, an ambitious young pupil at the Paris Opera Ballet, struggles to keep herself and her dreams alive when the Franco-Prussian War breaks out.
5.6
5-8
Keywords: Ballet dancers -- Fiction; Paris (France) -- Fiction; Art appreciation -- Fiction; Historical fiction; Ballet dancers -- Fiction; Paris (France) -- Fiction; Art appreciation -- Fiction; Historical fiction